Kr–Cl stretching vibration of HKrCl: Matrix-isolation and anharmonic ab initio study - Lignell, Antti; Lundell, Jan; Pettersson, Mika; Khriachtchev, Leonid; Räsänen, Markku (Физика низких температур, 2003)
The Kr–Cl stretching vibration of HKrCl molecule is studied. The absorption shows ³⁵Cl and ³⁷Cl isotopic splitting due to natural abundance of the Cl isotopes. The observed Kr–Cl stretching vibrations of the HKrCl are at 253.1 (³⁵Cl) and 248.3 cm–¹ (³⁷Cl). Deuteration of the HKrCl does not cause experimentally a shift of the Kr–Cl stretching frequency. In addition to the Kr–Cl stretching mode, the bending mode of DKrCl is observed at 397.7 cm–¹. The vibrational analysis suggests that the Kr–Cl bond show, in addition to ionic, some covalent character. Anharmonic ab initio calculations are employed to verify vibrational properties of various isotopologues of HKrCl.